Effect of Oral Administration of Dehydroepiandrosterone on PCOS-Like Phenotype of Female C57BL/6 Mice - Sundari, Ayu Mulia; Prakoso, Nurul Muhammad; Dwiranti, Astari; Abinawanto, Abinawanto; Boediono, Arief; Funahashi, Hiroaki; Bowolaksono, Anom (Universitas Bengkulu, 2024)
We aim to evaluate the efficacy and optimal dose of orally administered DHEA in the PCOS mice model by assessing their ovarian morphology and serum FSH, LH, and testosterone levels. Female C57BL/6 mice were divided into a control group (n=5, received daily injections of 0.2 ml sesame oil) and an experimental group, which was further classified into 1) D-45 group (n=5), 2) D-60 (n=5), and 3) D-90 group (n=5) that were treated with 45, 60, and 90 mg/Kg body weight of oral DHEA. After modelling, mice in the control group had a regular estrous cycle, while mice in all experimental groups had a disturbed estrous cycle. Ovarian histology showed several growing follicles and some corpora lutea (CL) in the control, D-60, and D-90 groups. However, some large antral follicles and decreased CL were observed in the D-45 group. Serum FSH was significantly lower in the D-45 group than in the control group (3.73 ± 0.12 vs. 5.28 ± 0.31 mIU/mL, P<0.01), but D-60 and D-90 groups had a similar FSH level to the control group (P>0.05). The serum level of LH and testosterone were significantly elevated in the D-45 group than in the control group (2.52 ± 0.43 vs. 1.30 ± 0.33 mIU/mL, P<0.01 and 1.80 ± 0.32 vs. 1.24 ± 0.23 ng/mL, P<0.01, respectively). Still, the level of LH and testosterone in the D-60 and the D-90 groups was comparable to the control group (P>0.05). Our study suggests that oral administration of DHEA is efficacious in establishing PCOS-like phenotype in mice with the suggested optimal dosage of 45 mg/Kg body weight.